High-Tc superconductivity : the excitonic coulomb perspective - Luo, Nie; Miley, George H. (George Hunter), 1933- (Singapore : Jenny Stanford Publishing, 2021)
The exciton mechanism of high-Tc superconductivity in copper oxides was initially proposed by Prof. J. Bardeen. His insight is largely shared by another luminary in superconductivity, Prof. V. L. Ginzburg. The main author of the book, Dr. Nie Luo, was motivated by their insights to give a geometrical explanation to the excitonic Coulomb interaction and has developed a unique formalism to understand and predict physical properties of high-Tc superconductors. This work is supported by increasingly strong evidence for electron-hole interactions in p-type cuprates. The presence of electrons in hole-doped cuprates is revealed by the works of the authors and many others, including the late Prof. L. P. Gor'kov. The book also tries to understand the interlayer Coulomb (ILC) pairing model by the excitonic Coulomb interaction. Developed by Prof. A. J. Leggett, ILC theory shares many views with Ginzburg's approach. The other author of the book, Prof. George H. Miley, shares with us his personal experience with Prof. Bardeen on the exciton's role in physics problems including high-Tc superconductivity. The results and predictions of this excitonic Coulomb mechanism have been verified by an increasing number of experiments. This book summarizes the current status and fathoms future directions.
OCLC-licensed vendor bibliographic record.
Keywords: Copper oxide superconductors; High temperature superconductivity; Coulomb excitation; SCIENCE / Physics; SCIENCE / Quantum Theory; SCIENCE / Mechanics / Dynamics / Thermodynamics